Neuroprotective properties of novel substituted glyprolines in vitro - T. A. Antipova; K. N. Kolyasnikova; Y. S. Volkova; P. I. Antipov; E. A. Kuznetsova; S. V. Nikolaev (LLC "Publisher OKI", 2019)
Resume. Previously in the Zakusov Institute of Pharmacology the linear substituted glyproline GZK-111, N-phenylacetyl-glycyl-L-proline ethyl ester, which is capable to convert into the neuropeptide cyclo-prolylglycine (CPG) in biological media and displaying the nootropic, anxiolytic, antihypoxic and neuroprotective activity, was designed and synthesized. The aim of the work was to study the neuroprotective activity of analogues of substituted glyproline GZK-111 at the C- and N-terminus in vitro on the oxidative stress model in comparison to the GPG. Oxidative stress caused by H2O2 (1.5 mM) led to significant decrease in the hippocampal cells HT-22 viability. L-CPG protected cells against H2O2 in concentrations up to 10-7M when applied both 24 h before and immediately after damage. The compound with an open carboxylic group (GZK-115) like CPG protected HT-22 cells from death in both experimental schemes at concentrations up to 10-7M. The substituted amide GZK-119 added 24 h before cell damage, had a cytoprotective effect at a concentration of 10-7M, and after peroxide damage in concentrations of 10-6 - 10-7M. The D-enantiomer of ethyl ester N-phenylacetyl-glycyl-proline (GZK-121) and the compound with the extension of the N-acyl fragment to the CH2-group (GZK-45) were effective at concentrations up to 10-6M in both experimental schemes. Simultaneous extension of the N-acyl fragment to the CH2 group and replacement of the ester with an amide (GZK-50) resulted to protection of the cells from death only after H2O2. Thus, it was established that all investigated substituted glyprolines possessed neuroprotective activity in experiments in vitro under conditions of oxidative stress in HT-22 cells. The most active compounds were GZK-119 and GZK-115.